Automatically binding relevant and irrelevant features in visual working memory. - Zhao, Chenxiao; Li, Xinyu; Failing, Michel; Wang, Benchi (Quarterly Journal of Experimental Psychology, 2022)
It is generally assumed that, to save storage space, features are stored as integrated objects in visual working memory (VWM). Although such an object-based account does not always hold because features can be processed in parallel, a previous study has shown that different features can be automatically bound with their locations (task-irrelevant feature) into an integrated unit, resulting in improved memory performance. The present study was designed to further explore this phenomenon by investigating whether other features, which are not spatial in origin, can act as the binding cue to form such automatic binding. To test this, we used three different features as binding cues (i.e., colour, spatial frequency, and shape) over multiple separate experiments. The results consistently showed that when two features shared the same binding cue, memory performance was better relative to when each of those features had their own binding cue. We conclude that any task-irrelevant feature can act as a binding cue to automatically bind with task-relevant features even across different objects, resulting in memory enhancement.